ศึกษาการปฏิบัติกรรมฐานตามแนวพระเทพวิสุทธิมงคล (ศรี มหาวีโร) - โพธิญาณรัตน, พระพุทธะมหาภาศสมจิตโตมหามุณี; วิมล, พระราชปริยัติวิมล (วารสารศรีล้านช้างปริทรรศน์, 2016)
วิทยานิพนธ์เรื่องนี้มีจุดประสงค์ ดังต่อไปนี้ 1) เพื่อศึกษาการปฏิบัติกรรมฐานตามแนวพุทธปรัชญาเถรวาทโดยทั่วไป 2) เพื่อศึกษาการปฏิบัติกรรมฐานตามแนวพระเทพวิสุทธิมงคล (ศรี มหาวีโร) และ 3) เพื่อวิเคราะห์การปฏิบัติกรรมฐานตามแนวพระเทพวิสุทธิมงคล (ศรี มหาวีโร) โดยศึกษาจากเอกสารปฐมภูมิ คือ พระไตรปิฎก และเอกสารทุติยภูมิ ได้แก่ อรรถกถา หนังสือ เอกสาร และงานวิจัยที่เกี่ยวข้อง   ผลการวิจัยพบว่า การปฏิบัติกรรมฐานตามแนวพุทธปรัชญาเถรวาทโดยทั่วไปนั้น จึงเป็นประพฤติปฏิบัติทางด้านจิตใจ หรือเป็นงานของใจ ในพระพุทธศาสนาได้ให้ความสำคัญของจิตใจ เพราะใจเป็นใหญ่ ใจเป็นประธาน เมื่อจิตใจสงบ จิตใจก็เป็นสมาธิ เมื่อยกใจจากสมาธิให้สูงขึ้นด้วยการพิจารณาก็จะเกิดปัญญา เกิดความรู้แจ้งแทงตลอด การปฏิบัติกรรมฐานตามแนวพุทธปรัชญาเถรวาท จึงเป็นงานของใจโดยเฉพาะ การปฏิบัติกรรมฐานตามแนวพระเทพวิสุทธิมงคล (ศรี มหาวีโร) จึงเป็นการปฏิบัติกรรมฐานตามแนวพุทธปรัชญาเถรวาท คือ การสวดมนต์ไหว้พระ ทำวัตรเช้า ทำวัตรเย็นเพื่อระลึกถึงคุณของพระพุทธเจ้า พระธรรมเจ้า พระสังฆเจ้า การพิจารณากรรมฐานขั้นพื้นฐานที่ได้รับมาจากพระอุปัชฌาย์ พิจารณาความไม่สวยงามของร่างกาย พิจารณาปัจจัยสี่ การพิจารณามหาสติปัฏฐานสี่ คือ การนั่ง การเดิน การยืน เป็นต้น การศึกษาวิเคราะห์การปฏิบัติกรรมฐานตามแนวพระเทพวิสุทธิมงคล (ศรี มหาวีโร) จึงทำให้ทราบว่า การปฏิบัติกรรมฐานตามแนวพระเทพวิสุทธิมงคล (ศรี มหาวีโร) นั้นได้เริ่มตั้งแต่พรรษาแรกจนถึงพรรษาที่ 43 และแบ่งออกเป็นช่วงๆ ช่วงแรก คือพรรษาที่ 1 ถึง 17 เป็นการปฏิบัติกรรมฐานแบบ สมถกรรมฐาน เมื่อได้สมาธิสูงสุดแล้วก็ทำให้สมาธิเสื่อม หลวงปู่ศรี มหาวีโร จึงได้ยกระดับสมาธิขึ้นเป็นวิปัสสนากรรมฐาน คือ เข้าถึงความรู้แจ้ง เห็นจริงแห่งสังขารตามกฎของไตรลักษณ์ The purposes of this thesis were: 1) to study practices of meditation in Theravada Buddhism, 2) to study those based upon the approaches of Phra Thepvisuddhimongkol (Sri Mahaviro), 3) to analyze those based upon his approaches. It was the qualitative research whereby its data were collected from Tipitaka and relevant texts. The results of the research were found that: The practices of meditation in general in Theravada Buddhism have to do with mind, the task of training it to be calm. The practices of meditation put the main emphasis on training it since one’s mind is regarded as the prime master and the subject of all deeds. The fact in point is when one’s mind has become absolutely calm. It is far too easy to proceed to concentration. In practice, when the level of mind is raised from concentration to the higher level through meditation, it gains insight into realization. In other words, the practice of meditation in Theravada Buddhism is the only matter of mind in particular. The practice of meditation performed by Phra Thepvisuddhimongkol (Sri Mahaviro) was exactly the same as those in Theravada Buddhism. As a matter of his daily routine when performing his mental meditation at dawn and before dust, his undertakings were: paying homage to Triple Gems, reciting discourses (Sutras) to recall Triple Gems’ great contribution, performing his preceptor’s fundamental meditation by taking into account the impermanence of his physique, paying attention to proper consumption for four necessities of life, and focusing on one of four foundations of mindfulness (Satipatthana) in order to raise awareness of sitting, standing and lying, etc. The analytical study on practices of meditation based upon his approaches made it clear that his whole time of practices was divided into two sessions, ranging from the first year of his monkhood to 43 th year.  His first session for pursuing mental meditation happened between the first and seventeenth years of his monkhood.  His last session was dedicated to performing insight meditation due to declines of concentration when his practice reached its highest state. Accordingly, he raised the level of his concentration on insight meditation, thereby succeeding in achieving realization and truth of compounded things (Sangkhara) conducive to Rule of Three Characteristics (Tilakkhana).